Hard carbon negative electrode composite material, preparation method and application thereof
By introducing cores of graphite, metal oxides and heteroatoms and shell structures of amorphous carbon into the hard carbon negative electrode material, the problems of poor electronic conductivity, energy density and first-time efficiency of existing hard carbon negative electrode materials in sodium ion batteries are solved, and the specific capacity and power performance are improved.
Patent Information
- Application Number
- CN202510323853.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
Existing hard carbon anode materials show poor electronic conductivity, energy density and first-time efficiency in sodium ion batteries.
Hard carbon negative electrode composite material is used, the core material includes graphite, doped metal oxides and heteroatoms, and the shell material is amorphous carbon. Aerogel is formed by hydrothermal reaction and carbonization, followed by depositing amorphous carbon at high temperatures to coat the core.
The specific capacity, electronic conductivity and first-time Coulomb efficiency of hard carbon anode composite materials are improved, and the cycle stability and rate performance of the material are enhanced.
Smart Images

Figure CN119852382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a hard carbon negative electrode composite material, a preparation method and application thereof. Background Art
[0002] As the market's requirements for the energy density and power performance of sodium-ion batteries increase, the hard carbon negative electrode materials used in sodium-ion batteries are required to have high specific capacity while also improving their fast charging and power performance. Currently, the hard carbon materials on the market are mainly prepared by solidifying and carbonizing biomass or resins. Their porous structure causes large impedance due to the insertion and extraction of sodium ions, which reduces their rate performance. In addition, the sodium storage capacity of carbon-based materials is limited, making it difficult to significantly increase the specific capacity of hard carbon. Alloy materials formed by metal elements and sodium ions have the characteristics of specific capacity, such as tin, cerium, molybdenum and other metals, which have good power performance, but have large expansion, so the materials need to be modified and coated to reduce their expansion.
[0003] Although the specific capacity of the negative electrode materials currently used in the market has been improved, the power improvement is limited and the initial efficiency has not improved. Summary of the invention
[0004] The main purpose of the present invention is to propose a hard carbon negative electrode composite material, a preparation method and its application, aiming to solve the problems of poor electronic conductivity, energy density and initial efficiency of hard carbon in the prior art.
[0005] To achieve the above object, the present invention provides a hard carbon negative electrode composite material, comprising a core and a shell covering at least a portion of the outer surface of the core; Wherein, the material of the inner core includes graphite, and metal oxides and heteroatoms doped in the graphite, the metal oxides include at least sodium oxide, and the metal oxides can react with sodium to form a sodium alloy material; The material of the shell includes amorphous carbon.
[0006] In one embodiment, in the hard carbon negative electrode composite material, the mass ratio of the material of the core to the material of the shell is (80-95): (5-20); and / or, In the core material, the mass ratio of the metal oxide to the heteroatom particles is (1-5): (1-5); and / or, The metal oxide further comprises antimony trioxide or antimony pentoxide; and / or, The heteroatom includes at least one of nitrogen, phosphorus and sulfur.
[0007] The present invention also provides a method for preparing a hard carbon negative electrode composite material, comprising the following steps: S10, mixing a metal compound, a sodium salt, a carbon source, an ionic liquid and an oxidant, performing a hydrothermal reaction, and freeze-drying to obtain a first aerogel; S20, mixing the first aerogel of step S10 with a heteroatom mixed gas and performing a carbonization treatment to obtain a second aerogel; S30, cooling the second aerogel in step S20, and then mixing it with a carbon source gas to deposit amorphous carbon, thereby obtaining the hard carbon negative electrode composite material.
[0008] In step S10: The mass ratio of the metal compound, the sodium salt, the carbon source and the oxidant is (1-5): (5-15): 100: (0.5-2); and / or, The metal compound comprises at least one of antimony acetate, antimony citrate, antimony lactate and potassium antimony tartrate; and / or, The sodium salt comprises at least one of sodium 3-aminobenzenesulfonate, sodium m-aminobenzenesulfonate, sodium p-hydroxybenzoate and sodium p-toluenesulfonate; and / or, The carbon source comprises at least one of glucose, sucrose, maltose and lactose; and / or, The oxidant includes one of methyl ethyl ketone peroxide, lauroyl peroxide, cyclohexanone peroxide and benzoyl peroxide.
[0009] In one embodiment, in step S10, the ionic liquid includes at least one of N-methylimidazole sodium nitrate, N-ethylimidazole sodium nitrate, 1-aminopropyl-3-methylimidazole sodium bromide, 1-aminoethyl-3-methylimidazole sodium bromide and 1-aminopropyl-3-methylimidazole sodium nitrate.
[0010] In one embodiment, in step S20: The heteroatom mixed gas includes nitrogen and other gases, and the other gases include at least one of ammonia, phosphine and hydrogen sulfide, wherein the volume ratio of the nitrogen to the other gases is (10:1~5) and the inlet flow rate of the heteroatom mixed gas includes 100-300SCCM.
[0011] In one embodiment, in step S20, in the step of performing carbonization treatment: The temperature of the carbonization treatment is 800-1200°C; and / or, The carbonization treatment time is 1-6h.
[0012] In one embodiment, in step S30: The carbon source gas includes at least one of methane, ethane, ethylene and acetylene, and the flow rate of the carbon source gas includes 100-300 SCCM; and / or, The deposition temperature of the deposited amorphous carbon is 700-1000°C.
[0013] In one embodiment, in step S30, the temperature of the second aerogel is reduced to 700-900°C.
[0014] The present invention also provides an application, in which the aforementioned hard carbon negative electrode composite material or the hard carbon negative electrode composite material prepared by the aforementioned hard carbon negative electrode composite material preparation method is applied to a sodium ion battery.
[0015] In the technical solution of the present invention, the hard carbon negative electrode composite material includes a core and a shell coated on at least part of the outer surface of the core, the core is doped with metal oxides, which serve as active centers to improve the electrochemical properties of the hard carbon material, and the metal oxides can react with sodium in the electrolyte to form sodium alloy materials during the charge and discharge process, which has a high specific capacity and improves the specific capacity of the hard carbon negative electrode composite material; the metal oxides include at least sodium oxide, which can increase the insertion and extraction rate of sodium ions during the charge and discharge process, and heteroatoms are doped in the core, which are covalently bonded / embedded into the core to improve the electronic conductivity of the material, and amorphous carbon is coated on the surface of the core to reduce the specific surface area, reduce side reactions, and improve the first coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0017] Figure 1 This is a scanning electron microscope image (SEM) of the hard carbon negative electrode composite material in Example 4 provided by the present invention.
[0018] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0019] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0020] As the market's requirements for the energy density and power performance of sodium-ion batteries increase, the hard carbon negative electrode materials used in sodium-ion batteries are required to have high specific capacity while also improving their fast charging and power performance. Currently, the hard carbon materials on the market are mainly prepared by solidifying and carbonizing biomass or resins. Their porous structure causes large impedance due to the insertion and extraction of sodium ions, which reduces their rate performance. In addition, the sodium storage capacity of carbon-based materials is limited, making it difficult to significantly increase the specific capacity of hard carbon. Alloy materials formed by metal elements and sodium ions have the characteristics of specific capacity, such as tin, cerium, molybdenum and other metals, which have good power performance, but have large expansion, so the materials need to be modified and coated to reduce their expansion.
[0021] Although the specific capacity of the negative electrode materials currently used in the market has been improved, the power improvement is limited and the initial efficiency has not improved.
[0022] In view of this, in order to achieve the above-mentioned object, the present invention provides a hard carbon negative electrode composite material, comprising a core, and a shell covering at least a portion of the outer surface of the core; Wherein, the material of the core includes graphite, and metal oxides and heteroatoms doped in the graphite, the metal oxides include at least sodium oxide, and the metal oxides can react with sodium to form a sodium alloy material; The material of the shell includes amorphous carbon.
[0023] In the technical solution of the present invention, the hard carbon negative electrode composite material includes a core and a shell coated on at least part of the outer surface of the core, the core is doped with metal oxides, which serve as active centers to improve the electrochemical properties of the hard carbon material, and at the same time, the metal oxides can react with sodium in the electrolyte during the charge and discharge process to form a sodium alloy material with a high specific capacity, thereby improving the specific capacity of the hard carbon negative electrode composite material; the metal oxides include at least sodium oxide, which can increase the insertion and extraction rate of sodium ions during the charge and discharge process, and heteroatoms are doped in the core, which are covalently bonded / embedded into the core to improve the electronic conductivity of the material, and amorphous carbon is coated on the surface of the core to reduce the specific surface area, reduce side reactions, and improve the first coulombic efficiency.
[0024] In some embodiments of the present invention, in the hard carbon negative electrode composite material, the mass ratio of the material of the core to the material of the shell is (80-95): (5-20). By regulating the mass ratio of the core to the shell material, the mechanical stability and electrochemical activity of the structures of the two can be optimized.
[0025] In the core material, the mass ratio of the metal oxide to the heteroatom particles is (1-5): (1-5). By rationally setting the ratio of metal oxide to heteroatom, active sites can be better provided while ensuring the integrity of the carbon skeleton structure and improving its electronic conductivity.
[0026] In some embodiments of the present invention, the metal oxide further comprises antimony trioxide or antimony pentoxide. Specifically, in the hydrothermal reaction, the organometallic compound (such as antimony acetate, antimony citrate, etc.) decomposes under high temperature and pressure to release antimony ions (Sb³ + These antimony ions interact with other reactants (such as carbon sources and oxidants) and may form antimony oxides (such as Sb2O3, Sb2O5) or form composite materials with carbon.
[0027] In some embodiments of the present invention, the heteroatom includes at least one of nitrogen, phosphorus, and sulfur, which can optimize the electrochemical properties of the hard carbon composite material, enhance conductivity, improve sodium storage performance, and optimize the pore structure.
[0028] The present invention also provides a method for preparing a hard carbon negative electrode composite material, comprising the following steps: S10, mixing a metal compound, a sodium salt, a carbon source, an ionic liquid and an oxidant, performing a hydrothermal reaction, and freeze-drying to obtain a first aerogel; S20, mixing the first aerogel with a heteroatom mixed gas and performing a carbonization treatment to obtain a second aerogel; S30, cooling the second aerogel and mixing it with a carbon source gas to deposit amorphous carbon to obtain the hard carbon negative electrode composite material.
[0029] In the technical solution of the present application, step S10 includes: mixing a metal compound, a sodium salt, a carbon source, an ionic liquid and an oxidant. Under hydrothermal conditions, the carbon source forms a cross-linked carbon network through polymerization reaction and dehydration condensation reaction, and a porous structure is initially constructed. The sodium salt promotes the decomposition of the carbon source through catalysis or complexation, thereby improving the formation efficiency of the carbon network. At the same time, the metal compound undergoes a redox reaction with the oxidant to generate a metal oxide or a metal hydroxide, which is partially dispersed in the cross-linked carbon network. In addition, the oxygen free radicals released by the oxidant can further promote the cross-linking of the carbon network to form a first aerogel with a three-dimensional porous structure. The metal oxide or metal hydroxide not only acts as an active center to improve the electrochemical properties of the hard carbon material, but also releases gas through subsequent heat treatment to further generate pores, providing more active sites for the embedding of sodium ions or sodium ions. At the same time, freeze drying is used to avoid the pore collapse caused by capillary forces in the traditional drying process, and the three-dimensional porous structure of the first aerogel is retained to the maximum extent.
[0030] In step S20, the first aerogel is treated with a heteroatom mixed gas for carbonization. Under high temperature conditions, the organic matter in the first aerogel decomposes, and the skeleton is converted into a carbon skeleton to form a more stable porous structure. At the same time, the heteroatoms are doped into the carbon skeleton by covalent bonding, embedding or surface modification at high temperature to form a second aerogel. The doping of heteroatoms significantly improves the conductivity of the carbon skeleton, while increasing the active sites for the embedding of lithium / sodium ions, further improving the specific capacity and cycle stability of the electrode material.
[0031] In step S30, the second aerogel of step S20 is cooled to avoid destroying the structure of the heteroatoms and the first aerogel, while also avoiding excessive decomposition of the carbon source. It is then mixed and decomposed with the carbon source gas at high temperature to deposit amorphous carbon on its surface, so that the amorphous carbon layer fills the pores of the second aerogel, thereby increasing the mass density of the hard carbon negative electrode composite material and enhancing the cyclic stability of the material. It also provides more lithium / sodium insertion sites and improves the sodium / lithium storage capacity.
[0032] In step S10: the mass ratio of the metal compound, the sodium salt, the carbon source and the oxidant is (1-5): (5-15): 100: (0.5-2). Within this mass range, the formation of aerogel is favorable, and the porosity and dispersibility of the first aerogel can be improved.
[0033] The metal compound includes at least one of antimony acetate, antimony citrate, antimony lactate and potassium antimony tartrate. The metal compound has good water solubility and dispersibility and is evenly distributed in the reaction system.
[0034] The sodium salt includes at least one of sodium 3-aminobenzenesulfonate, sodium m-aminobenzenesulfonate, sodium p-hydroxybenzoate and sodium p-toluenesulfonate. The sodium ions of the provided sodium salt can participate in the polymerization reaction and dehydration condensation reaction of the carbon source, promote the cross-linking formation of the carbon network, and the presence of the sodium salt makes the generated carbon aerogel have more porous structure, reduce the defects of the material core, reduce the irreversible capacity, and sufficient sodium ions increase the diffusion rate and insertion and extraction rate of sodium ions during the charge and discharge process, thereby improving the rate performance.
[0035] The carbon source includes at least one of glucose, sucrose, maltose and lactose. The carbon source is a polyhydroxy compound that is easily carbonized. After carbonization, a continuous three-dimensional cross-linked carbon network structure can be formed. Gas is released during the carbonization process, which is conducive to forming a porous structure and improving the specific surface area and sodium ion storage capacity.
[0036] The oxidant includes one of methyl ethyl ketone peroxide, lauroyl peroxide, cyclohexanone peroxide and benzoyl peroxide. The above oxidant participates in the hydrothermal reaction, so that the reaction rate of the carbon source and the metal compound is increased, and metal oxides or metal hydroxides are obtained and combined with the carbon skeleton. Part of the oxidant will decompose to produce gas, thereby increasing the specific surface area of the material.
[0037] In some embodiments of the present invention, in step S10, the ionic liquid includes at least one of N-methylimidazole sodium nitrate, N-ethylimidazole sodium nitrate, 1-aminopropyl-3-methylimidazole sodium bromide, 1-aminoethyl-3-methylimidazole sodium bromide and 1-aminopropyl-3-methylimidazole sodium nitrate.
[0038] It can be understood that ionic liquids have excellent solubility and structure-guiding effects, and can regulate the micropore distribution and skeleton strength of the carbon skeleton. The use of the above-mentioned ionic solution can ensure that the formed aerogel structure is uniform.
[0039] In some embodiments of the present invention, in step S20: The heteroatom mixed gas includes nitrogen and other gases, and the other gases include at least one of ammonia, phosphine and hydrogen sulfide, wherein the volume ratio of the nitrogen to the other gases is (10:1-5) and the flow rate of the heteroatom mixed gas includes 100-300 SCCM. The heteroatom gas can provide activity, and the flow rate is controlled to control the reaction rate, so as to ensure the uniformity of doping and the stability of the aerogel structure.
[0040] In some embodiments of the present invention, in step S20, in the step of performing carbonization treatment: The carbonization temperature is 800-1200°C, within which the aerogel can be completely carbonized while avoiding structural collapse due to excessively high temperatures. The carbonization time is 1-6h, which can ensure that the reaction is fully carried out and control energy consumption.
[0041] In some embodiments of the present invention, in step S30: The carbon source gas includes one of methane, ethane, ethylene and acetylene. The flow rate of the carbon source gas is 100-300 SCCM. By controlling the flow rate, the shell of the generated amorphous carbon is more uniform.
[0042] The deposition temperature of the deposited amorphous carbon is 700-1000° C. The addition of the carbon source gas can decompose at 700-1000° C. to generate amorphous carbon to cover the core.
[0043] Furthermore, in some embodiments of the present invention, in step S30, the second aerogel is cooled to 700-900° C. In this temperature range, graphitization of amorphous carbon can be avoided due to excessively high temperatures, and amorphous carbon can be uniformly deposited.
[0044] The present invention also provides an application, wherein the hard carbon negative electrode composite material or the hard carbon negative electrode composite material prepared by the preparation method of the hard carbon negative electrode composite material is applied to a sodium ion battery. The hard carbon negative electrode composite material has all the above-mentioned beneficial effects, which will not be described one by one here.
[0045] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0046] Example 1 A hard carbon negative electrode composite material, comprising a core and a shell covering at least a portion of the outer surface of the core; the material of the core comprises graphite and metal oxides and heteroatoms doped in the graphite; Wherein, the metal oxide includes antimony oxide; the heteroatom includes p; the mass ratio of the hard carbon to the amorphous carbon is 90:10; the mass ratio of the metal oxide to the heteroatom is 1:1.
[0047] Example 2 Example 2 is similar to Example 1, except that: The metal oxide includes antimony oxide; the heteroatom includes S, and the mass ratio of the hard carbon to the amorphous carbon is 95:5; the mass ratio of the metal oxide to the heteroatom is 1:5.
[0048] Example 3 Example 3 is similar to Example 1, except that: The metal oxide includes antimony oxide; the heteroatom includes S, the mass ratio of the graphite to the amorphous carbon is 80:20; the mass ratio of the metal oxide to the heteroatom is 5:1.
[0049] Example 4 A method for preparing a high-capacity and high-power hard carbon negative electrode composite material comprises the following steps: Step S10: adding 3 g of antimony acetate and 10 g of sodium 3-aminobenzenesulfonate to 1000 g of 10 wt% glucose in N-methylimidazole sodium nitrate solution, then adding 1 g of methyl ethyl ketone peroxide, and reacting by hydrothermal reaction at a temperature of 100 ° C and a pressure of 3 MPa for 3 h. The obtained material is freeze-dried at -40 ° C for 24 h to obtain a metal-doped carbon aerogel, i.e., the first aerogel; Step S20: the metal-doped aerogel is transferred to a tubular furnace, and argon inert gas is first introduced to exhaust the air in the tube, and then ammonia mixed gas (volume ratio, ammonia: nitrogen = 3:10) is introduced at a flow rate of 200 SCCM, and carbonized at a high temperature of 1000° C. for 3 h to obtain an intermediate material, i.e., the second aerogel; Step S30: Then, the introduction of the ammonia mixed gas is stopped, the temperature is lowered to 800° C., and ethylene gas is introduced at a flow rate of 200 SCCM for 150 min to deposit amorphous carbon on the surface of the intermediate, thereby obtaining a hard carbon negative electrode composite material.
[0050] Example 5 A method for preparing a high-capacity and high-power hard carbon negative electrode composite material comprises the following steps: Step S10: adding 1 g of antimony citrate and 5 g of sodium m-aminobenzenesulfonate to a 1000 g, 10 wt% sucrose N-ethylimidazole sodium nitrate solution, then adding 0.5 g of lauroyl peroxide, and reacting by hydrothermal reaction at a temperature of 80° C. and a pressure of 5 MPa for 6 h. The obtained material is freeze-dried at -40° C. for 24 h to obtain a metal-doped carbon aerogel, i.e., a first aerogel; Step S20: the metal-doped aerogel is transferred to a tubular furnace, argon inert gas is first introduced to exhaust the air in the tube, and then a phosphine mixed gas (volume ratio, phosphine: argon = 1:10) is introduced, and carbonization is performed at a high temperature of 800° C. and a flow rate of 100 SCCM for 6 hours to obtain an intermediate material, i.e., the second aerogel; Step S30: Then, stop introducing the phosphine mixed gas, cool down to 700° C., introduce acetylene gas at a flow rate of 100 SCCM for 300 min, deposit amorphous carbon on the surface of the intermediate, and obtain a hard carbon negative electrode composite material.
[0051] Example 6 A method for preparing a high-capacity and high-power hard carbon negative electrode composite material comprises the following steps: Step S10: adding 5 g of antimony lactate and 15 g of sodium p-hydroxybenzoate to a 1000 g, 10 wt% maltose 1-aminopropyl-3-methylimidazolium bromide sodium solution, then adding 2 g of cyclohexanone peroxide, and reacting by hydrothermal reaction at a temperature of 150° C. and a pressure of 1 MPa for 6 h. The obtained material is freeze-dried at -40° C. for 24 h to obtain a metal-doped carbon aerogel, i.e., a first aerogel; Step S20: the metal-doped aerogel is transferred to a tubular furnace, argon inert gas is first introduced to exhaust the air in the tube, and then a hydrogen sulfide mixed gas (volume ratio, hydrogen sulfide: argon = 5:10) is introduced, and carbonization is performed at a high temperature of 1200° C. and a flow rate of 300 SCCM for 1 hour to obtain an intermediate material, i.e., the second aerogel; Step S30: Then, stop introducing the hydrogen sulfide mixed gas, cool down to 900° C., introduce methane gas at a flow rate of 300 SCCM for 30 minutes, deposit amorphous carbon on the surface of the intermediate, and obtain a hard carbon negative electrode composite material.
[0052] Comparative Example 1 The difference from Example 4 is that antimony acetate and sodium 3-aminobenzenesulfonate are not added, that is, the metal oxide is removed, and the rest is the same as Example 4.
[0053] Comparative Example 2 The difference from Example 4 is that no ammonia mixed gas is introduced in step S20, that is, no heteroatom is doped, and the rest is the same as Example 4.
[0054] Performance Testing (1) SEM test The hard carbon negative electrode composite material prepared in Example 4 was subjected to SEM test, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the composite material presents a spherical structure and its particle size D 50 The size is around 5μm and the distribution is uniform.
[0055] (2) Physical and chemical properties and button cell battery testing The interlayer spacing (D002), specific surface area, and tap density of the hard carbon negative electrode composite materials prepared in Examples 4 to 6 and Comparative Examples 1-2 were tested in accordance with the national standard GB / T 43114-2023 "Hard Carbon"; the powder resistance was tested using a four-probe tester, and the grain size was tested and calculated using XRD. The test results are shown in Table 1.
[0056] The hard carbon negative electrode composite materials in Examples 4 to 6 and Comparative Examples 1-2 were used as negative electrode materials for sodium ion batteries and assembled into button cells. The specific preparation method of the negative electrode material was as follows: hard carbon negative electrode composite materials: CMC: SBR: SP: H2O were mixed in a mass ratio of 93:3:2:2:150 to obtain a negative electrode sheet; sodium sheet was used as the counter electrode; NaPF6 (solvent was EC: DEC: PC: propylene glycol polyoxypropylene ether = 1:2:1:0.05, concentration 1.3 mol / L) was used as the electrolyte; the diaphragm was a composite film of polyethylene PE, polypropylene PP and polyethylene propylene PEP. The button cell was assembled in an argon-filled glove box. The electrochemical performance was carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.00V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell were tested, and the rate performance (1C / 0.1C) of the button cell was tested. The test results are shown in Table 1.
[0057] Table 1 It can be seen from Table 1 that the hard carbon negative electrode composite materials prepared in Examples 4-6 are superior to those in Comparative Examples 1-2 in terms of powder conductivity, specific capacity, La, etc. The reason is that the materials are doped with antimony oxide metal compounds to form sodium alloy materials during the charge and discharge process, thereby improving the specific capacity of the materials, and by doping with metal oxides, reducing their irreversible capacity, improving the initial efficiency and the diffusion rate of sodium ions, and improving the rate performance.
[0058] (3) Soft pack battery test: The hard carbon negative electrode composite materials in Examples 4-6 and Comparative Examples 1-2 were mixed and coated to prepare negative electrode sheets. 1 / 3 Mn 1 / 3 Ni 1 / 3 A 5Ah soft-pack battery was prepared using NaPF6 (the solvent was PC:EC:FEC=1:1:0.05, concentration 1.1 mol / L) as the positive electrode.
[0059] Test cycle performance: charge and discharge current 1.0C / 1.0C, voltage range 1-4.0V, cycle number 500 times.
[0060] Test rate performance: Constant current ratio under 2C charging conditions = 2C constant current capacity / (2C constant current capacity + 0.1C constant voltage capacity).
[0061] The test results are shown in Table 2.
[0062] Table 2
[0063] It can be seen from Table 2 that compared with the comparative example, the cycle performance of Examples 4-6 is significantly better than that of Comparative Examples 1~2. The reasons for this are as follows: compared with Comparative Examples 1~2, the metal oxides and heteroatoms doped in the example materials, the heteroatoms can increase the lattice defects of the original hard carbon material or form a new crystal phase, which will increase the distance between the carbon layers. At the same time, the presence of the metal oxides can prevent the close stacking of the carbon layers, thereby obtaining a large interlayer spacing to reduce expansion and improve the cycle performance; the introduction of heteroatoms and metal oxides into the example materials can disrupt the ordered arrangement in the carbon matrix, prevent the stacking and growth of the carbon layers, help maintain a smaller grain size and a lower powder resistivity, thereby improving the constant current ratio of the hard carbon negative electrode composite material.
[0064] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A hard carbon negative electrode composite material, characterized in that: comprising a core, and a shell covering at least a portion of the outer surface of the core; Wherein, the material of the inner core includes graphite, and metal oxides and heteroatoms doped in the graphite, the metal oxides include at least sodium oxide, and the metal oxides can react with sodium to form a sodium alloy material; The material of the shell includes amorphous carbon.
2. The hard carbon negative electrode composite material according to claim 1, characterized in that In the hard carbon negative electrode composite material, the mass ratio of the material of the core to the material of the shell is (80-95): (5-20); and / or, In the core material, the mass ratio of the metal oxide to the heteroatom is (1-5): (1-5); and / or, The metal oxide further comprises antimony trioxide or antimony pentoxide; and / or, The heteroatom includes at least one of nitrogen, phosphorus and sulfur.
3. A method for preparing a hard carbon negative electrode composite material as claimed in claim 1 or 2, characterized in that: The following steps are involved: S10, mixing the metal compound, the sodium salt, the carbon source, the ionic liquid and the oxidant, performing a hydrothermal reaction, and freeze-drying to obtain a first aerogel; S20, mixing the first aerogel of step S10 with a heteroatom mixed gas, and performing a carbonization treatment to obtain a second aerogel; S30, cooling the second aerogel in step S20, and then mixing it with a carbon source gas to deposit amorphous carbon, thereby obtaining the hard carbon negative electrode composite material.
4. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S10: The mass ratio of the metal compound, the sodium salt, the carbon source and the oxidant is (1-5): (5-15): 100: (0.5-2); and / or, The metal compound comprises at least one of antimony acetate, antimony citrate, antimony lactate and potassium antimony tartrate; and / or, The sodium salt comprises at least one of sodium 3-aminobenzenesulfonate, sodium m-aminobenzenesulfonate, sodium p-hydroxybenzoate and sodium p-toluenesulfonate; and / or, The carbon source comprises at least one of glucose, sucrose, maltose and lactose; and / or, The oxidant includes one of methyl ethyl ketone peroxide, lauroyl peroxide, cyclohexanone peroxide and benzoyl peroxide.
5. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S10, the ionic liquid includes at least one of N-methylimidazole sodium nitrate, N-ethylimidazole sodium nitrate, 1-aminopropyl-3-methylimidazole sodium bromide, 1-aminoethyl-3-methylimidazole sodium bromide and 1-aminopropyl-3-methylimidazole sodium nitrate.
6. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S20: The heteroatom mixed gas includes nitrogen and other gases, and the other gases include at least one of ammonia, phosphine and hydrogen sulfide, wherein the volume ratio of the nitrogen to the other gases is 10: (1-5), and the inlet flow rate of the heteroatom mixed gas includes 100-300 SCCM.
7. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S20, in the step of carbonization treatment: The temperature of the carbonization treatment is 800-1200°C; and / or, The carbonization treatment time is 1-6h.
8. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S30: The carbon source gas includes at least one of methane, ethane, ethylene and acetylene, and the flow rate of the carbon source gas includes 100-300 SCCM; and / or, The deposition temperature of the deposited amorphous carbon is 700-1000°C.
9. The method for preparing the hard carbon negative electrode composite material according to claim 3, characterized in that: In step S30, the second aerogel is cooled to 700-900°C.
10. An application, characterized in that: The hard carbon negative electrode composite material as claimed in claim 1 or 2 is applied to a sodium ion battery.
Citation Information
Patent Citations
Antimony oxide / nitrogen doped graphene composite material, and preparation method and application thereof
CN110190256A
Modified hard carbon negative electrode material for sodium ion battery and preparation method of modified hard carbon negative electrode material
CN116154175A
Hard carbon composite material for high-safety sodium ion battery and preparation method of hard carbon composite material
CN117096311A
Modified hard carbon composite material for sodium ion battery as well as preparation method and application of modified hard carbon composite material
CN117317191A
Negative electrode material, preparation method thereof and sodium ion battery
CN117497754A
Cited By
NaF-doped hard carbon negative electrode composite material as well as preparation method and application thereof
CN121460545A